FRI0177 Biologic Drug Initiators: Real World Patterns of Monotherapy and Combination Therapy after One Year. (10th June 2014) - Reed, G.; Ganguli, A.; Saunders, K.; Magner, R.; Greenberg, J.D.
Abstract : Background: Little is known regarding the treatment practices of rheumatologists with respect to biologic initiation as monotherapy versus combination therapy with nonbiologic disease modifying anti-rheumatic drugs (nbDMARDs) such as methotrexate (MTX). We explored treatment patterns at the time of biologic initiation as well as 1 year after initiation. Methods: In a large US patient registry (CORRONA), we identified patients with a diagnosis of rheumatoid arthritis who were initiated on their first biologic between 10/2001-9/2012. Patients at time of initiation are divided into three therapy groups: Biologic Monotherapy - no other nbDMARD (Mono); Combination Therapy with a nbDMARD (Combo-nbDMARD) which could be MTX (Combo-MTX); or another nbDMARD (Combo-non-MTX DMARD). Patients using MTX + another nbDMARD are included in Combo-MTX. Patient demographic and clinical characteristics are estimated within each group. Within each therapy group, those initiators with a one year follow-up visit (1 year ±2 months from initiation) are divided into their current therapy at one year. Results: The CORRONA registry, as of 9/3/2012, had 33, 959 RA patients with at least one clinical visit. There were 3, 987 patients who initiated their first biologic among biologic naïve RA patients. Of these initiations, monotherapy represented 18%, combination therapy with MTX in 69%, and combination with a non-MTX nbDMARD in 13%. Demographic and clinical characteristics were similar among the three therapy groups of Mono, Combo-MTX, Combo-non-MTX DMARD: Average Age (57.0, 57.3, 58.1), CDAI (21.4, 21.2, 20.2), mHAQ (0.51, 0.49, 0.49). Average duration of disease was higher in the Combo-nbDMARD (9.7 yrs) vs Combo-MTX (7.8 yrs, p<0.001) and Mono groups (8.4yrs, p=0.02). Combo-MTX had 95.9% with prior use of MTX while Mono and Combo-nbDMARD had 70.7% and 70.6%, respectively. As shown in Figure 1, between 22 and 30% of patients in each category were not on biologic therapy at the one year follow-up. The majority of Combo-MTX and Combo-non-MTX DMARD users were still on combination therapy at 1 year while only 45% of monotherapy users still received a biologic without a nbDMARD. Of the Combo-MTX group, 55.6% remained on exactly the same medications while only 36.1% for Mono and 37.3% for Combo-DMARD. Conclusions: Rheumatologists initiate biologic agents in combination with nbDMARDs in the majority of patients with most persisting on combination therapy at 1 year. Additionally, one-quarter of monotherapy users switched to combination therapy during follow-up. Of note, a substantial number of biologic initiators, regardless of monotherapy or combination nbDMARD initiation discontinued biologic therapy. Acknowledgements: The CORRONA RA registry has been supported through contracted subscriptions in the last 2 years by AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Eli Lilly, Novartis, Pfizer, Vertex and UCB. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: G. Reed Employee of: CORRONA, Inc., A. Ganguli Shareholder of: AbbVie, Employee of: AbbVie, K. Saunders Employee of: CORRONA, Inc., R. Magner Employee of: UMASS Medical School, J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca, Pfizer, Employee of: CORRONA, Inc. DOI: 10.1136/annrheumdis-2014-eular.1544